Graphene oxide enhanced, radiation cross-linked, vitamin E stabilized oxidation resistant UHMWPE with high hardness and tensile properties. Issue 87 (7th December 2017) - Pang, Wenchao; Wu, Jialiang; Zhang, Qifan; Li, Guangfei
Abstract : A method for enhancing the micro-hardness and tensile properties of cross-linked ultrahigh molecular weight polyethylene (UHMWPE) by radiation cross-linking after adding vitamin-E (VE) and graphene oxide (GO) was reported. Abstract : A method for enhancing the micro-hardness and tensile properties of cross-linked ultrahigh molecular weight polyethylene (UHMWPE) for total joint implants by radiation cross-linking after adding vitamin-E (VE) and graphene oxide (GO) was reported in this paper. Vitamin E was blended with UHMWPE powder at a concentration of 0.1 wt%, followed by adding GO at a concentration of 0.5 wt% and subsequently irradiated with 60 Co gamma-rays at 100 kGy. The GO/VE/UHMWPE composite showed improved micro-hardness (∼8%), Young's modulus (∼28%), yield stress (∼33%) and fracture stress (∼37%) in comparison with UHMWPE. The OI of irradiated UHMWPE decreased from 1.9 to 0.7 after blending with VE and the OI of irradiated VE/UHMWPE increased from 0.7 to 1.3 after filling with GO. In addition, the addition of GO further reduced the gel content.